2014
DOI: 10.5539/jel.v3n2p52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group Work on EFL Students’ Attitudes and Learning in Higher Education

Abstract: The use of group work in classroom activities is a method used for motivating learning and increasing the idea of pleasure through learning. The current study investigates the advantages of group work in exams in the English department, in the College of Basic Education. 40 students in two classes of "The Introduction of Phonetics and Phonology" participated in the study. They performed six tasks; two prior to group work, two done in group work (by one group only) and two after group work. The tasks were all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 26 publications
5
35
0
Order By: Relevance
“…Hence, it is necessary to make the classroom learning atmosphere be conducive by reducing the gap between two different groups of EFL students and creating fun learning atmosphere for all students in a bicultural class in order to achieve their EFL learning objective. This is in line with Taqi and Al-Nouh (2014) who found that group work increases the idea of pleasure through learning.…”
Section: Learning Habitssupporting
confidence: 91%
See 3 more Smart Citations
“…Hence, it is necessary to make the classroom learning atmosphere be conducive by reducing the gap between two different groups of EFL students and creating fun learning atmosphere for all students in a bicultural class in order to achieve their EFL learning objective. This is in line with Taqi and Al-Nouh (2014) who found that group work increases the idea of pleasure through learning.…”
Section: Learning Habitssupporting
confidence: 91%
“…Since this study is concerned with EFL students of a bicultural class encountering some cultural differences which further causes learning challenges between those coming from two different cultural backgrounds, cooperative learning by which they can improve motivation (Pan & Wu, 2013;Ning & Hornby, 2014), and promote high level of achievement (Tran, 2014), and widen their social interaction (Laguador, 2014) among themselves is considerably implemented. This means that it is necessary for them to have Group Discussion as part of cooperative learning (Johnson, Johnson, & Smith, 1998) which was proved to be beneficial to be implemented in EFL classroom (Taqi and Al-Nouh, 2014), working in groups, students get the chance to expand their thought processes and simultaneously maximize communication with their peers (Othman and Murad, 2015). In order to come to the fluidity of the EFL students coming from two different cultural backgrounds, the discussion should be in the format of an inter and intra-culture based group discussion.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some researchers have expressed their perspectives to the fact that working in groups can affect positively on lower students" feeling in classrooms, some other researchers believe that working together in groups can inhibit their motivation (see Taqi & Al-Nouh, 2014). For instance, the dominance of certain group members can be the main drawback of working in a group (Taqi & Al-Nouh, 2014). Therefore, teachers should be aware that group work will not become a practical solution to address the anxiety issue if it is not conducted correctly and monitored carefully.…”
Section: Promoting Cooperative Learning Atmospherementioning
confidence: 99%